Prediction of tool life and experimental investigation during hot milling of AISI H13 tool steel - Amin, A. K. M. Nurul; Hafiz, A.M.K.; Lajis, M.A.; Patwari, Anayet U. (Trans Tech Publications, Switzerland, 2010)
This paper presents the results of experimental investigations conducted on a vertical machining centre (VMC) using spindle speed, feed rate, and depth of cut as machining variables to ascertain the effectiveness of TiAlN insert in end milling of hardened steel AISI H13, under workpiece preheated conditions and hence a statistical model was developed using the capabilities of Response Surface Methodology (RSM) to predict the tool life. Sufficient number of experiments was conducted based on the small central composite design (CCD) concept of RSM to generate tool life data for the selected machining variables. The adequacy of the model was tested at 95% confidence interval. Meanwhile, a time trend was observed in residual values between model predictions and experimental data, reflecting little deviations in tool life prediction. A very good performance of the RSM model, in terms of agreement with experimental data, was achieved. The model can be used for the analysis and prediction of the complex relationship between cutting conditions and the tool life in flat end milling of hardened materials.